(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2024)
The exodus of Rohingya refugees in Indonesia has occurred since 2009 until today. The Government of Indonesia has made various efforts to help the Rohingya refugees. Zakat funds have been allocated to fulfill the refugees’ basic life requirements. This study employs a qualitative approach, utilizing a literature review to explore the role of zakat-system crowdfunding in collecting funds, explicitly concentrating on programs initiated by the National Zakat Agency (BAZNAS) for Rohingya refugees in Indonesia. Secondary data from prior research, diverse sources, journals, books, and the internet form the basis of this investigation, employing the triangulation technique to ensure data reliability. The findings underscore the vital role of zakat as humanitarian aid for Rohingya refugees, contributing to social justice, equilibrium, guarantees, and safety. However, the existing zakat distribution primarily addresses immediate needs, necessitating long-term empowerment programs for the refugees’ independence. A proposed model introduces a crowdfunding zakat system, offering a more efficient and transparent approach to collecting and distributing zakat to those in need. Additionally, the study presents an Integrated Zakat and Waqf Model for Refugees (IZWMR), amalgamating institutional and individual donations into a charity pooling fund. This model prioritizes basic needs fulfillment, entrepreneurship training, and microenterprise development, with cash waqf playing a crucial role in subsidizing profit margins and invigorating refugee businesses. Ultimately, these proposed models aim to elevate the welfare of Rohingya refugees in Indonesia, not only providing immediate relief but also empowering them with the tools for self-sufficiency and independence.